Stratigraphy and Petrography of the Tual - Puruay volcanic sequence Puruay - Lluscapampa Traverse (South of Yanacocha) Cajamarca – Peru - Esparza Pérez, Edwin Phelipe (2022)
The hamlets of Puruay Bajo and Lluscapampa Baja are located north of the city of Cajamarca at Km. 4.5 of the Cajamarca - Bambamarca highway; in this area we determined the different volcanic stages of pyroclastic flows of the Tual - Puruay Pyroclastic Volcanic sequence and the third stage of the San José sequence, these rocks belong to the Yanacocha Volcanic Complex of Neogene Miocene age (23.03 - 5.3 Ma). This complex is divided into Volcanic Sequences: Tual Puruay, Atazaico Volcanic Center, Regalado Volcanic Center and San José. The geological mapping was carried out with the respective sections that helped in the elaboration of stratigraphic columns. In addition, samples were collected where we proceeded to carry out the petrographic study either in thin section (SD) and polished section (SP) of the most representative ones. With the stratigraphic columns, petrographic studies and observations of the rocky outcrops, conclusions were reached that a period of time where explosive volcanism occurred generated pyroclastic rocks, these in turn are subject to sedimentation stages, forming pseudo strata of volcanic composition, these would indicate facies change in the development of active volcanism in the lower Miocene 20 Ma ago.